Peranan Politik Etnisitas Dalam Kontestasi Pemilu di Indonesia - Agustini, Wanda Qori; David, David; Arzikah, Sahliah Dita (Journal of Citizenship, 2024)
Abstract: Indonesia as one of the countries that has wealth in the form of quite a lot of diversity in the world, this is supported by the many differences between different individuals within one country, one of these differences is motivated by differences in race or ethnicity. According to the 2010 Statistics Agency census, there were 1,340 ethnic groups in Indonesia. This ethnic diversity is the identity of the Indonesian nation and a differentiator from other nations. But on the other hand, in fact this diversity also creates problems for our nation, one of which is when the election is approaching. It is often found that parties selling the issue of ethnicity in election contests which in turn lead to divisions and groupings between ethnicities, this problem is not a new problem in Indonesia, the issue of ethnicity existed long before the reform era.Keywords: Ethnicity, Election, DiversityÂ Abstrak: Indonesia sebagai salah satu negara yang memiliki kekayaan berupa keanekaragaman yang cukup banyak di dunia, hal ini didukung oleh banyaknya perbedaan antar individu yang bebeda di dalam satu negara, salah satu perbedaan tersebut dilatar belakangi oleh adanya perbedaan ras ataupun etnis. Menurut sensus Badan Statistik pada tahun 2010 tercatat ada 1.340 jumlah etnis yang ada di Indonesia, adanya keanekargaman etnis ini menjadi identitas bangsa Indonesia dan menjadi pembeda dari bangsa-bangsa lain. Namun di sisi lain nyatanya keanekaragam ini juga menimbulkan adanya persoalan bagi bangsa kita, salah satunya yakni ketika menjelang pemilu. Seringkali ditemukannya pihak-pihak yang menjual isu etnisitas di dalam kontestasi pemilu yang pada akhirnya menimbulkan perpecahan serta pengelompokan antar etnis, permasalahan ini memang bukan menjadi persoalan baru di Indonesia, isu etnisitas sudah ada jauh sebelum masa reformasi.Kata Kunci: Etnisitas, Pemilu, Keanekaragaman